Influencia de pre tratamientos convencionales en el proceso de secado de banano y en las características físicas del producto final - Castro, Paul (2010)
This objective was to evaluate the effects of pre-drying treatments such as osmotic dehydration, antioxidants, and blanching using banana. A dry samples with different pre-treatments were performed to obtain the isotherms of the monolayer, which has a direct relationship with the shelf life. Once drying processes, it was determined the rate of drying where the product has the highest rate of drying is that which was not subjected to any pre-treatment, which is related to life. Subsequently, in addition to the experiment, we determined the shelf life, using the method of Theodore Labuza, proving the relationship and the value of the monolayers of the isotherms and the values of drying rate, which the sample without pre-treatment showed the highest value. Finally, we statistically analyzed the results, with a design of experiments, comparing the response variables with a significance level of 95%.